A novel sludge pyrolysis and biomass gasification integrated method to enhance hydrogen-rich gas generation. (15th February 2022) - Li, Aishu; Han, Hengda; Hu, Song; Zhu, Meng; Ren, Qiangqiang; Wang, Yi; Xu, Jun; Jiang, Long; Su, Sheng; Xiang, Jun
Graphical abstract: Highlights: A novel sludge pyrolysis and biomass gasification integrated method is proposed. More H2 was obtained at 50% moisture content due to a synergistic effect. This synergy transforms N from nitriles to amines, which then condense to N-PAHs. 268 mL/g H2 was obtained by the integrated method with a calcium-based additive. Abstract: A novel sludge pyrolysis and biomass gasification (SPBG) integrated method is proposed to facilitate the efficient utilization of sludge and biomass. The transformation of gas, especially hydrogen, and the migration of N in SPBG were investigated. The H2 proportion increased by 6.22 vol% due to the involvement of sludge steam (S-steam) and sludge volatiles (S-volatiles). S-steam was beneficial to gasification, reforming, and the water–gas shift (WGS) reaction of biomass, which was conducive to hydrogen production. Moreover, in the gasification stage, S-volatiles were heated and then cracked to form gases and free radicals. The latter changed the original system to facilitate dehydrogenization with condensation and the formation of new functional groups. In the range of 30–70%, when the moisture content of the wet sludge was 50%, a relatively higher amount of H2 and a higher calorific value were obtained. To further enhance hydrogen production, a modified calcium-based additive (MCA) was added. At 800 °C, the addition of MCA promoted steam reforming and the WGS reaction, resulting in a higher H2 concentration of 268.31 mL/g (based on dehydrated feeding including sludge volatiles and biomass). Nitrogen-containing functional groups such as amines, N-PAH, and nitriles from tar also decreased after the addition of MCA.